Zawartość metali ciężkich w glebach terasy zalewowej Odry w okolicy Huty Miedzi "Głogów" i Bytomia Odrzańskiego = The heavy metal content in soils of the flooded terrace in the vicinity of "Głogów" copper smeltery and Bytom Odrzański - Greinert, Henryk (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the soils of the flooded terrace of the Odra river in the vicinity of Capper Smeltery ''Głogów" and Bytom Odrzański the contents of Pb, Cd, Zn, and Cu were determined. By the capper smelter the soils were under the influence of the dust pollution from this plant, but in Bytom Odrzański the was not the case. The cooper and lead content was in BytomOdrzański distinctly, lower as near the cooper smelter however, the zinc and cadmium content did not differ in the both localities. It is the evidence, that the river water transported this more soluble pollutants from beside copper smelter "Głogów".
Keywords: 2 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zagospodarowanie zlewni" (21-22.06.2001)